Memory and hope: new perspectives on the Kashmir conflict – an introduction. (October 2014) - Mathur, Shubh
The guest editorial of the special section of the journal argues that one should not view the conflict as simply a territorial dispute between India and Pakistan, but as experienced by Kashmiris as the heavily militarised control of everyday life (which means disappearances, unmarked mass graves, torture and rape carried out by armed forces with impunity). It is those inside Kashmir who can provide the possible solutions to the conflict. The author provides a historical background to the State of Jammu and Kashmir from the 1846 Treaty of Amritsar, through decolonisation and the refusal to hold the promised plebiscite on Kashmir's future, to the rise of militant insurgency. It situates in current conditions the articles that follow: by Nyla Ali Khan (on her grandfather Prime Minister Sheikh Abdullah and the 1953 coup); Gowhar Geelani (on not letting the world forget Kashmir); Jim Drummond (on the political use of the death penalty); Sajid Iqbal (on the possibility of transitional justice); Noor Ahmad Baba (on the potential for political solutions); and Gull Wani (on sub-regional contradictions and devolved power).